2013
DOI: 10.3201/eid1901.111640
|View full text |Cite
|
Sign up to set email alerts
|

Seropositivity for Influenza A(H1N1)pdm09 Virus among Frontline Health Care Personnel

Abstract: Seroprevalence of antibodies to influenza A(H1N1)pdm09 virus among 193 emergency department health care personnel was similar among 147 non–health care personnel (odds ratio 1.4, 95% CI 0.8–2.4). Working in an acute care setting did not substantially increase risk for virus infection above risk conferred by community-based exposures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
16
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(19 citation statements)
references
References 13 publications
(15 reference statements)
2
16
1
Order By: Relevance
“…A study comparing seropositivity among emergency department healthcare workers and non-healthcare workers in New York found seroprevalence of 21% among healthcare workers, and no difference in seroprevalence was detected between healthcare workers and non-healthcare workers. 30 An Australian study similarly found no difference in seroprevalence between clinical and non-clinical tertiary hospital employees; 31 and a Hong Kong study found no difference in seroprevalence between hospital staff and communitybased blood donors. 32 A study of healthcare workers and managers in Scottish hospitals found an influenza A(H1N1)pdm09 seroprevalence of 10.3% at the pandemic peak.…”
Section: Comparison With Existing Literaturementioning
confidence: 96%
“…A study comparing seropositivity among emergency department healthcare workers and non-healthcare workers in New York found seroprevalence of 21% among healthcare workers, and no difference in seroprevalence was detected between healthcare workers and non-healthcare workers. 30 An Australian study similarly found no difference in seroprevalence between clinical and non-clinical tertiary hospital employees; 31 and a Hong Kong study found no difference in seroprevalence between hospital staff and communitybased blood donors. 32 A study of healthcare workers and managers in Scottish hospitals found an influenza A(H1N1)pdm09 seroprevalence of 10.3% at the pandemic peak.…”
Section: Comparison With Existing Literaturementioning
confidence: 96%
“…soldiers; RR = 0.26, CI = 0.07 to 0.46) [23]. Six high quality studies [32][33][34][35][36][37] and one moderate quality study [43] showed no significantly higher or lower risk of influenza A (H1N1) infection for HCP in comparison with non-HCP.…”
Section: Study Characteristicsmentioning
confidence: 97%
“…Prevalence rates among controls/comparisons ranged between 1.0% and 30.0%. Nine high quality [16,26,[29][30][31][33][34][35]37] and two moderate quality [38,39] studies showed higher H1N1 prevalence rates for HCP compared to controls/comparisons. Based on the eight quality criteria, fourteen studies (70%) were of high quality (!…”
Section: Study Characteristicsmentioning
confidence: 98%
See 2 more Smart Citations